Z analizo podatkovnih baz do trajnih informacij o znanosti - Artus, Helmut M. (Organizacija znanja, 2008)
Databases are more than just registers providing bibliographic information because of the research history they contain. Database research involves five areas: management, usage, analysis, history/sociology and methodology /epistemology. A distinction is made between a structural and sociological aspect of databases. The example of SOLIS database development illustrates the significance of database history. Sociology reveals to what extent data is socially conditioned, whereby the influence of the relations within research organisations is of importance as well. An epistemological database analysis tells more than a statistical analysis as it may reveal that not direct science but rather pre-screened and indexed data retrieved from other databases is analysed. In this way "soft" data is becoming "hard" data or, actually, artefacts. Consequently, database search without intellectual control involves risks, and if the intellectual control is not exerted in database analysis either, this can only result in artefacts. Database researchers must have an interdisciplinary approach and they must be familiar not only with their "own" discipline but also with database informatics, or they will not be able to distinguish between permanent and other information within databases.
Keywords: analize; podatkovne zbirke; raziskovanje; SOLIS